Yogurt Republic Reels Strategy by “Socially Zee Media” for Yogurt Republic Sales - Muhammad Dyka Zulfaqqar; Farida Nurfalah (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2026)
This study examines the Instagram Reels content strategy implemented by Socially Zee Media (SZM) in promoting Yogurt Republic as a form of relevant digital marketing in the social media era. The objectives of this study include describing the Instagram Reels content strategy in creating brand awareness for Yogurt Republic, understanding the role of social media algorithms in expanding Yogurt Republic’s audience reach, analyzing SZM’s Reels content strategy in creating the Yogurt Republic brand image, and applying the Hierarchy of Effects theory, which explains the stages of audience awareness leading to action. The research method uses a descriptive qualitative approach through in-depth interviews, content observation, and digital documentation to explore SZM’s creative strategies and audience responses. Consumer interest and perception, as well as purchase intent, are positively influenced by storytelling and visual elements such as color, advertising, and ad design. Reels also reflect Instagram report analyses and position video content according to Generation Z consumers’ binge-watching patterns and as a visual storytelling medium. Although Reels do not have a direct or significant impact on sales growth, they do influence brand awareness, engagement, and brand preference. This research concludes the initial statement that SZM’s digital marketing strategy utilizing Reels is an effort to position and formulate the marketing potential of SMEs effectively, clearly emphasizing a consistent and creative visual image and/or impression to drive purchase intent.